SMS alert for level of fertilizer in fertigation tanks / Md Rizal Ramli - Ramli, Md Rizal (2012)
Technology never stands still. From the existence of Silicon Valley in the late 60's, technology has developed in rapid phase until now. Among the most radical innovations of all time is the introduction of mobile phones. Mobile phones have also developed from just a communication tool into a miniature PC. Lots of applications have been developed to be used in a mobile phone. However, the most common usage of mobile phones is Short Messaging System (SMS). SMS Alert for Level of Fertilizer in Fertigation Tanks is a project developed to exploit SMS services. This project uses a GSM Module to act as a transmitter. GSM Module has been pre-programmed using a PIC to alert users of a condition of fertilizer tank via SMS. This project is also applicable to be used to monitor water dams, septic tanks and other kinds of water container. SMS Alert for Level of Fertilizer in Fertigation Tanks is one of application that can be utilized using SMS technology. The system could detect a level of the fertilizer in the tank hence would alert user via SMS. Infra-Red Distance Sensor would detect the length of fertilizer level inside the tank. The system microprocessor would send a signal to user via a GSM module and user would receive a SMS indicating a few levels of fertilizer detection. The microprocessor in the system would constantly monitor the sensors' input and report back the situation to the user when needed.